HARMONIZING TRADITIONAL AND MODERN VALUES IN THE EDUCATIONAL PROCESS - Keldiyorova Manzura G’aybullayevna; Raxmatova Gulruh Hamroyevna (Bright Mind Publishing, 2025)
This article discusses the methods of harmonizing traditional and modern values in the educational process and delivering our national customs to the future generation.The article also reflects on how modern knowledge and national values for educators who began their early career in education can also effectively apply innovation, to study their creative approach through innovative educational methods.
Keywords: Tradition, value, modern knowledge, motivation and inspiration.